UNKNOWN Questions

Question Number 69735 by mhmd last updated on 27/Sep/19

$$\underset{\:\mathrm{0}} {\overset{\pi/\mathrm{4}} {\int}}\:\frac{\mathrm{sin}\:{x}+\mathrm{cos}\:{x}}{\mathrm{3}+\mathrm{sin}\:\mathrm{2}{x}}\:{dx}\:= \\$$

Commented by mathmax by abdo last updated on 27/Sep/19

$${I}=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\:\frac{{sinx}+{cosx}}{\mathrm{3}+{sin}\left(\mathrm{2}{x}\right)}{dx}\:\Rightarrow\:{I}\:=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\:\frac{{sinx}+{cosx}}{\mathrm{3}+\mathrm{2}{sinx}\:{cosx}}{dx} \\$$$$=_{{tan}\left(\frac{{x}}{\mathrm{2}}\right)={t}} \:\:\:\:\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\:\frac{\frac{\mathrm{2}{t}}{\mathrm{1}+{t}^{\mathrm{2}} }+\frac{\mathrm{1}−{t}^{\mathrm{2}} }{\mathrm{1}+{t}^{\mathrm{2}} }}{\mathrm{3}+\mathrm{2}\frac{\mathrm{2}{t}}{\mathrm{1}+{t}^{\mathrm{2}} }×\frac{\mathrm{1}−{t}^{\mathrm{2}} }{\mathrm{1}+{t}^{\mathrm{2}} }}\frac{\mathrm{2}{dt}}{\mathrm{1}+{t}^{\mathrm{2}} } \\$$$$=\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\:\:\:\:\frac{\mathrm{2}{t}+\mathrm{1}−{t}^{\mathrm{2}} }{\left(\mathrm{1}+{t}^{\mathrm{2}} \right)^{\mathrm{2}} \left\{\mathrm{3}+\frac{\mathrm{4}{t}\left(\mathrm{1}−{t}^{\mathrm{2}} \right)}{\left(\mathrm{1}+{t}^{\mathrm{2}} \right)^{\mathrm{2}} }\right\}}\left(\mathrm{2}{dt}\right. \\$$$$=\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\:\frac{−\mathrm{2}{t}^{\mathrm{2}} +\mathrm{4}{t}+\mathrm{2}}{\mathrm{3}\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} +\mathrm{4}{t}−\mathrm{4}{t}^{\mathrm{3}} }{dt}\:=\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\frac{−\mathrm{2}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{2}}{\mathrm{3}\left({t}^{\mathrm{4}} +\mathrm{2}{t}^{\mathrm{2}} +\mathrm{1}\right)+\mathrm{4}{t}−\mathrm{4}{t}^{\mathrm{3}} }{dt} \\$$$$=\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\:\frac{−\mathrm{2}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{2}}{\mathrm{3}{t}^{\mathrm{4}} \:+\mathrm{6}{t}^{\mathrm{2}} \:+\mathrm{3}+\mathrm{4}{t}−\mathrm{4}{t}^{\mathrm{3}} }{dt}\:=\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\:\frac{−\mathrm{2}{t}^{\mathrm{2}} +\mathrm{4}{t}+\mathrm{2}}{\mathrm{3}{t}^{\mathrm{4}} −\mathrm{4}{t}^{\mathrm{3}} \:+\mathrm{6}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{3}}{dt} \\$$$${the}\:{roots}\:{of}\:\mathrm{3}{t}^{\mathrm{4}} −\mathrm{4}{t}^{\mathrm{3}} \:+\mathrm{6}{t}^{\mathrm{2}} \:+\mathrm{4}{t}\:+\mathrm{3}\:{are} \\$$$${t}_{\mathrm{1}} =\mathrm{1}+\mathrm{1},\mathrm{4142}{i}\:\:\left({complex}\right) \\$$$${t}_{\mathrm{2}} =\mathrm{1}−\mathrm{1},\mathrm{4142}{i}\left({complex}\right) \\$$$${t}_{\mathrm{3}} =−\mathrm{0},\mathrm{3333}+\mathrm{0},\mathrm{4714}{i}\:\left({complex}\right) \\$$$${t}_{\mathrm{4}} =−\mathrm{0},\mathrm{3333}−\mathrm{0},\mathrm{4714}{i}\left({complex}\right)\:\Rightarrow \\$$$${F}\left({t}\right)=\frac{−\mathrm{2}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{2}}{\mathrm{3}{t}^{\mathrm{4}} −\mathrm{4}{t}^{\mathrm{3}} \:+\mathrm{6}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{3}}\:=\frac{−\mathrm{2}{t}^{\mathrm{2}} \:+\mathrm{4}{t}\:+\mathrm{2}}{\left({t}−{t}_{\mathrm{1}} \right)\left({t}−\overset{−} {{t}}_{\mathrm{1}} \right)\left({t}−{t}_{\mathrm{2}} \right)\left({t}−\overset{−} {{t}}_{\mathrm{2}} \right)} \\$$$$=\frac{−\mathrm{2}{t}^{\mathrm{2}} \:+\mathrm{4}{t}+\mathrm{2}}{\left({t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{1}} \right){t}\:\:+\mid{t}_{\mathrm{1}} \mid^{\mathrm{2}} \right)\left({t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{2}} \right){t}\:+\mid{t}_{\mathrm{2}} \mid\right)} \\$$$$=\frac{{at}\:+{b}}{{t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{1}} \right){t}\:+\mid{t}_{\mathrm{1}} \mid^{\mathrm{2}} }\:+\frac{{bt}\:+{d}}{{t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{2}} \right){t}\:+\mid{t}_{\mathrm{2}} \mid^{\mathrm{2}} }\:\Rightarrow \\$$$$\int\:{F}\left({t}\right){dt}\:=\int\:\:\:\frac{{at}+{b}}{{t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{1}} \right){t}+\mid{t}_{\mathrm{1}} \mid^{\mathrm{2}} }{dt}\:+\int\:\:\frac{{bt}+{d}}{{t}^{\mathrm{2}} −\mathrm{2}{Re}\left({t}_{\mathrm{2}} \right){t}\:+\mid{t}_{\mathrm{2}} \mid^{\mathrm{2}} }{dt} \\$$$$....{be}\:{continued}... \\$$

Answered by Kunal12588 last updated on 27/Sep/19

$${I}=\int\frac{{sin}\:{x}\:+\:{cos}\:{x}}{\mathrm{3}\:+\:{sin}\:\mathrm{2}{x}}{dx} \\$$$${let}\:{sin}\:{x}\:−\:{cos}\:{x}\:=\:{t} \\$$$$\Rightarrow\left({sin}\:{x}\:+\:{cos}\:{x}\right)\:{dx}\:=\:{dt} \\$$$${t}^{\mathrm{2}} =\mathrm{1}−\mathrm{2}{sin}\:{x}\:{cos}\:{x}\:=\mathrm{1}−{sin}\:\mathrm{2}{x} \\$$$$\Rightarrow{t}^{\mathrm{2}} −\mathrm{4}=−\mathrm{3}−{sin}\:\mathrm{2}{x} \\$$$${x}\rightarrow\mathrm{0}\Rightarrow{t}\Rightarrow−\mathrm{1} \\$$$${x}\rightarrow\frac{\pi}{\mathrm{4}}\Rightarrow{t}\Rightarrow\mathrm{0} \\$$$${I}=\int\frac{{dt}}{\mathrm{2}^{\mathrm{2}} −{t}^{\mathrm{2}} }=\frac{\mathrm{1}}{\mathrm{4}}{log}\mid\frac{\mathrm{2}+{t}}{\mathrm{2}−{t}}\mid+{c} \\$$$$\underset{\:\mathrm{0}} {\overset{\pi/\mathrm{4}} {\int}}\:\frac{\mathrm{sin}\:{x}+\mathrm{cos}\:{x}}{\mathrm{3}+\mathrm{sin}\:\mathrm{2}{x}}\:{dx}\:=\frac{\mathrm{1}}{\mathrm{4}}\left[{log}\mid\frac{\mathrm{2}+{t}}{\mathrm{2}−{t}}\mid\right]_{−\mathrm{1}} ^{\mathrm{0}} \\$$$$=\frac{\mathrm{1}}{\mathrm{4}}\left\{\mathrm{0}−{log}\mathrm{1}+{log}\mathrm{3}\right\}=\frac{\mathrm{1}}{\mathrm{4}}{log}\mathrm{3} \\$$